Does video feedback & peer observation offer a valid method of reinforcing oral presentation training for undergraduate biochemists?. Issue 1 (1st January 2019) - Simpson, Timothy; Holden, Kathryn; Merrick, Deborah; Dawson, Simon; Bedford, Lynn
ABSTRACT: Presentations assessing public speaking skills are common features of undergraduate curricula. Performance feedback has often been traditionally limited to staff, yet students acting as peer assessors can also be a useful feedback source. Additionally, video recording offers a feedback method that can overcome a presentation's transience and empower a student's self-analysis. During 2016–17 a new 1st year module, ' Core Skills in Biochemistry ', was implemented at the University of Nottingham. Peer assessment and video feedback were trialled as augmentations to lecturer-sourced presentation feedback. Student opinions were surveyed to gauge efficacy. Results indicate video feedback was appreciated to a greater extent than peer feedback, and both focussed on body language. As the year progressed students felt less confident in their colleagues' judgement, and their willingness to receive peer feedback decreased. These results confirmed the validity of including these techniques within ' Core Skills ', and laid the foundation for further innovations currently being trialled.